Retinal Arterial Macroaneurysms: Clinical, Angiographic, and Tomographic Description and Therapeutic Management of a Series of 14 Cases. Issue 1 (January 2016) - Cahuzac, Armelle; Scemama, Claire; Mauget-Faÿsse, Martine; Sahel, José-Alain; Wolff, Benjamin
Purpose: To describe clinical, angiographic, and tomographic features and the therapeutic management of patients with retinal arterial macroaneurysm (RAM). Methods: Retrospective analysis of patients diagnosed with RAM between January 2011 and September 2014 in Professor Sahel's Department of Ophthalmology, Rothschild Foundation. Retinal arterial macroaneurysms were classified as hemorrhagic, exudative, or quiescent. Patient demographics and comorbidities were recorded. All patients underwent complete ophthalmologic examination including initial and final visual acuity (Early Treatment Diabetic Retinopathy Study chart), slit-lamp biomicroscopy, fundus examination, color and autofluorescence fundus imaging, fluorescein and indocyanine green angiography, and spectral-domain optical coherence tomography. Treatments were recorded. Results: Fourteen RAMs of 14 patients were included: 9 hemorrhagic and 5 exudative. The most severe clinical picture was associated with the hemorrhagic form. Exudative cases had a progressive onset and a better visual prognosis. Direct laser photocoagulation was performed in 4 cases, anti-vascular endothelial growth factor (VEGF) intravitreal injection in 4 cases, combined treatment (YAG laser + argon laser + anti-VEGF intravitreal injection) in 1 case, and 5 cases received no treatment. Conclusions: Retinal arterial macroaneurysm management should be specialized and rapid. Multimodal imaging should be performed for classifying it, assessing its prognosis and determining the most suitable treatment.